2018
DOI: 10.1016/j.jpainsymman.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Neurofeedback on Symptom Burden and Interference in Patients With Chronic Chemotherapy-Induced Neuropathy: Analysis of a Randomized Controlled Trial

Abstract: NFB appears to result in long-term reduction in multiple CIPN symptoms and improved postchemotherapy QOL and fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
(26 reference statements)
0
34
0
Order By: Relevance
“…See Tables 3, 4 for a summary of the pain and brain activity outcomes for all the studies. In another RCT, a sample of 71 cancer survivors with CIPN were randomly allocated to the NF group (n = 35) or to a waitlist control group (n = 36) (Prinsloo et al, 2018). A qEEG was conducted and used to develop patient-specific NF protocols to normalize EEG-assessed oscillation power.…”
Section: Evidence Regarding the Effects Of Eeg-based Nfmentioning
confidence: 99%
“…See Tables 3, 4 for a summary of the pain and brain activity outcomes for all the studies. In another RCT, a sample of 71 cancer survivors with CIPN were randomly allocated to the NF group (n = 35) or to a waitlist control group (n = 36) (Prinsloo et al, 2018). A qEEG was conducted and used to develop patient-specific NF protocols to normalize EEG-assessed oscillation power.…”
Section: Evidence Regarding the Effects Of Eeg-based Nfmentioning
confidence: 99%
“…40 All experimental studies were randomized controlled trials (RCTs). 40,41,43 The observational studies consisted of 1 prepost study 38 and 2 case reports. 39,42 Three studies reported on results of patients with breast cancer, 38,39,42 2 studies on populations with heterogeneous diverse cancer epidemiology, but more than 71% breast cancer survivors.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…39,42 Three studies reported on results of patients with breast cancer, 38,39,42 2 studies on populations with heterogeneous diverse cancer epidemiology, but more than 71% breast cancer survivors. 40,41 One study was conducted with pediatric brain tumor survivors. 43 Sample sizes ranged from 71 to 82 for the experimental studies and from 1 to 23 for the observational studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…NF treatment protocols can be designed either to upregulate or downregulate the oscillations at the targeted cortical networks. Several studies have investigated the clinical effectiveness of EEG-based NF in various populations include headaches, complex regional pain syndromes (CRPS-1), chemotherapy-induced peripheral neuropathy (CIPN), central neuropathic pain in paraplegia, fibromyalgia, postoperative pain, and cancer pain (Gorini, Marzorati, Casiraghi, Spaggiari, & Pravettoni, 2015;Hassan, Fraser, Conway, Allan, & Vuckovic, 2015;Jensen, Grierson, Tracy-Smith, Bacigalupi, & Othmer, 2007;Prinsloo et al, 2018;Santoro & Cronan, 2014). These studies generally used protocols to upregulate frequencies in the higher ranges (12-15 Hz) and inhibit theta (4-7 Hz) and high beta (22-30 Hz) for reducing pain severity (Santoro & Cronan, 2014).…”
Section: Introductionmentioning
confidence: 99%